Ecg-kit: a Matlab Toolbox for Cardiovascular Signal Processing. Issue 1 (4th April 2016) - Demski, Andrés Julio; Llamedo Soria, Mariano
The electrocardiogram kit ( ecg-kit ) for Matlab is an application-programming interface (API) developed to provide users a common interface to access and process cardiovascular signals. In the current version, the toolbox supports several ECG recording formats, most of them used by the most popular databases, which allows access to more than 7 TB of information, stored in public databases such as those included in Physionet or the THEW project. The toolbox includes several algorithms frequently used in cardiovascular signal processing, such as heartbeat detectors and classifiers, pulse detectors for pulsatile signals and an ECG delineator. In addition, it provides a tool for manually reviewing and correcting the results produced by the automatic algorithms. The results obtained can be stored in a Matlab (.MAT) file for backup or subsequent processing, or used to create a PDF report.